Urban food subsidies reduce natural food limitations and reproductive costs for a wetland bird - Betsy A. Evans (Nature Portfolio, 2020)
Abstract There is a strong conservation need to understand traits of species that adapt to urban environments, but results have been equivocal. Wetland birds exhibit a strong phylogenetic signal towards urban tolerance; however, they have largely been ignored in urban studies. In their historic ranges, wetland birds inhabit dynamic systems, traveling long distances to locate food. This ability to exploit dynamic resources may translate to success in urban environments, areas characterized by novel food opportunities. We used the Wood Stork (Mycteria americana), a species of conservation concern, to determine if the ability to exploit resources in natural environments translated to exploitation of urban resources. During optimal natural foraging conditions, storks nesting in both urban and natural wetlands had narrow diet breadths and high productivity. However, during suboptimal conditions, urban stork diet expanded to include anthropogenic items, leading to increased productivity. Our study provides a mechanistic understanding of how a wetland species persists, and even thrives, in urban environments. We demonstrated that species inhabiting dynamic systems can exploit urban areas resulting in increased reproductive performance during suboptimal conditions. Together, urban environments may support biodiversity in a variety of ways, but species-specific mechanistic understanding will help highlight how to best mitigate potential threats of urbanization.